2016
DOI: 10.1002/star.201500290
|View full text |Cite
|
Sign up to set email alerts
|

The impact of heat‐moisture treatment on the molecular structure and physicochemical properties of Coix seed starches

Abstract: The effects of heat‐moisture treatment on structure and properties of big Coix seed (BCS), translucent Coix seed (TCS), and small Coix seed (SCS) starches were investigated in this study. The amylose contents of BCS, TCS, and SCS starches were 0.63, 24.12, and 0.96%, respectively. After HMT, starches appeared cracks and broken, birefringence weakened and the relative crystallinity and the ratio of 1047 cm−1/1022 cm−1 of HMT starches decreased, owing to disorganization of double helices and disruption of crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 49 publications
0
15
0
2
Order By: Relevance
“…formation. Mechanical pretreatment of starch samples led to defect accumulation in the crystal structure, thus causing the disruption of double helices of amylopectin and single helices of amylase due to the rupture of hydrogen or glycosidic bonds, as well as the release of interspersed amylose molecules into the amorphous phase ( Figure 6) [10,26,[35][36][37]. It was shown that longer duration of mechanical activation leads to gradual amorphization of the crystalline structure of A-, B-, and C-type starches, so their crystallinity degree decreases.…”
Section: Resultsmentioning
confidence: 99%
“…formation. Mechanical pretreatment of starch samples led to defect accumulation in the crystal structure, thus causing the disruption of double helices of amylopectin and single helices of amylase due to the rupture of hydrogen or glycosidic bonds, as well as the release of interspersed amylose molecules into the amorphous phase ( Figure 6) [10,26,[35][36][37]. It was shown that longer duration of mechanical activation leads to gradual amorphization of the crystalline structure of A-, B-, and C-type starches, so their crystallinity degree decreases.…”
Section: Resultsmentioning
confidence: 99%
“…mayuen Stapf ) and has attracted wide attention from researchers in food and medicine fields due to its beneficial effects on health. Studies have shown that coix seed is rich in starch [ 17 ], proteins [ 18 ], free amino acids, dietary fibers [ 19 ], vitamins, minerals, phytosterols, and flavonoids [ 20 , 21 , 22 ] and has a high nutritional value. Clinically, coix seed is also widely applied in arthritis, diarrhea, diuretics, and pain relief [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that HMT increased RS level in various carbohydrate sources. For instance, the RS content in red rice starch (Hung et al ., 2020), mung bean starch (Li et al ., 2011), wheat starch/flour (Chen et al ., 2015), corn starch (Chung et al ., 2010; Zhou et al ., 2020), millet starch (Amadou et al ., 2014), potato starch (De La Rosa‐Millán, 2017; Hung et al ., 2017; Brahma & Sit, 2020), barley starch (Liu et al ., 2019), pea starch (Chung et al ., 2009), coix starch (Liu et al ., 2016) and breadfruit starch (Tan et al ., 2017) with HMT modification was higher than native. On the contrary, other studies reported that RS content in lily bulb starch (Li et al ., 2020), banana starch (Hoyos‐Leyva et al ., 2015), water caltrop starch (Wei et al ., 2020), pea starch (Chung et al ., 2010) and sweet potato starch (Huang et al ., 2016) with HMT modification was lower than native.…”
Section: Introductionmentioning
confidence: 99%